Genome-Wide Analysis of Gene Expression Provides New Insights into Cold Responses in Thellungiella salsuginea - Wang, Jiangshan; Zhang, Quan; Cui, Feng; Hou, Lei; Zhao, Shuzhen; Xia, Han; Qiu, Jingjing; Li, Tingting; Zhang, Ye; Wang, Xingjun; Zhao, Chuanzhi (Frontiers in Plant Science, 2017)
Low temperature is one of the major environmental stresses that affects plant growth and development, and leads to decrease in crop yield and quality. Thellungiella salsuginea (salt cress) exhibits high tolerance to chilling, is an appropriate model to investigate the molecular mechanisms of cold tolerance. Here, we compared transcription changes in the roots and leaves of T. salsuginea under cold stress using RNA-seq. We identified 2,782 and 1,430 significantly differentially expressed genes (DEGs) in leaves and roots upon cold treatment, respectively. The expression levels of some genes were validated by quantitative real-time-PCR (qRT-PCR). Among these DEGs, 159 (11.1%) genes in roots and 232 (8.3%) genes in leaves were annotated as various types of transcription factors. We found that five aquaporin genes (three TIPs, one PIPs and one NIPs) responded to cold treatment. In addition, the expression of COR47, ICE1, and CBF1 genes of DREB1/CBF-dependent cold signaling pathway genes altered in response to low temperature. KEGG pathway analysis indicated that these cold regulated genes were enriched in metabolism, photosynthesis, circadian rhythm, and transcriptional regulation. Our findings provided a complete picture of the regulatory network of cold stress response in T. salsuginea. These cold-responsive genes could be targeted for detail functional study and utilization in crop cold tolerance improvement.